Approaching Religious Symbols in the Public Space: Contemporary Art and Museums as Places of Negotiation? Journal for Religion, Film and Media - Daria Pezzoli-Olgiati (Journal for Religion, Film and Media, 2015)
This essay responds to Sigrid Schade's contribution by outlining the multilayered meaning-making processes deployed by the use of religious symbolism in visual culture. Referring in a concise way to a selected example of contemporary art, it drafts possible methodological approaches to a challenging field of research.